Present and Future of the E-Learning in Economics Schools and Faculties - T. Casasús Estellés; A. Ivars Escortell; M.I. López Rodríguez (Multidisciplinary Journal for Education, Social and Technological Sciences)
The goal of this paper is to justify/motivate the existence of MOOCs of quantitative subjects, particularly of Mathematics and Statistics, in the degrees taught in Faculties of Economics and Business, complementary to the standard university courses. The changes in curricula carried out in Spain in the last decade have boosted access to these faculties’ degrees for all kind of students. However, some of these students lack skills and abilities enough to successfully tackle the first university Mathematics and Statistics courses, as these are currently designed. Empirical studies support the use of multimedia material as a very effective supporting tool for successful learning.